2016
DOI: 10.1158/1078-0432.ccr-15-1883
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and Metabolic Features of Pancreatic Ductal Adenocarcinoma Define Prognostic Subtypes of Disease

Abstract: Purpose Pancreatic ductal adenocarcinoma (PDA) is associated with an immunosuppressive microenvironment that supports the growth of the malignancy as well as immune system evasion. Here we examine markers of immunosuppression in PDA within the context of the glycolytic tumor microenvironment, their inter-relationship with tumor biology and association with overall survival. Experimental design We utilized tissue microarrays consisting of 223 PDA patients annotated for clinical stage, tumor size, lymph node i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 49 publications
(64 reference statements)
3
68
1
Order By: Relevance
“…In contrast, the presence of macrophages (CD68 positive) and in particular M2 macrophages (CD163 positive) had negative effect on survival. These data are consistent with an emerging literature that the presence of tumor-associated macrophages (TAMs) is associated with more aggressive form of disease(40, 48). In addition to supporting tumor invasiveness and metastatic spread, TAMs inhibit T cell responses by production of indoleamine dioxygenase metabolites and reactive oxygen species and indirectly by recruiting regulatory T-cells to the tumor (49, 50).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the presence of macrophages (CD68 positive) and in particular M2 macrophages (CD163 positive) had negative effect on survival. These data are consistent with an emerging literature that the presence of tumor-associated macrophages (TAMs) is associated with more aggressive form of disease(40, 48). In addition to supporting tumor invasiveness and metastatic spread, TAMs inhibit T cell responses by production of indoleamine dioxygenase metabolites and reactive oxygen species and indirectly by recruiting regulatory T-cells to the tumor (49, 50).…”
Section: Discussionsupporting
confidence: 92%
“…Traditionally, the abundant desmoplastic stroma has been regarded as a barrier impairing tumor infiltration by TILs [3, 4]. Ino et al previously reported better outcome in patients with high stromal expression of CD8 [11], which is in agreement with our data but a recent work failed to detect a prognostic role for CD8+ TILs [32]. Also, even in tumors with high CD8+ TILs infiltration in the stroma, the majority of tumors lacked CD8+ TILs in the close proximity to cancer cells in our cohort.…”
Section: Discussionsupporting
confidence: 91%
“…Although work have assessed the prognostic impact of TILs and Tregs, and recently of PD-L1 [32], in PDAC, nevertheless, none of these studies examined in detail the association of all four immune markers with the desmoplastic stoma and their localization in large pancreatectomy sections. Traditionally, the abundant desmoplastic stroma has been regarded as a barrier impairing tumor infiltration by TILs [3, 4].…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, lactate suppresses natural killer and T cell anti-tumor immune responses [20, 101, 102]. Similarly, tumor-derived lactate drives macrophages toward an immunosuppressive fate [21, 103, 104]. In these contexts, lactate functions directly as a signaling molecule, though the contribution of lactate in this capacity relative to its role in metabolic pathway rewiring and microenvironment acidification have yet to be fully elucidated.…”
Section: Intra-tumoral Metabolic Crosstalkmentioning
confidence: 99%